Risk factors for hospital-acquired and community-acquired pressure injuries: a multicentre mixed case–control study. Issue 4 (18th April 2022) - Ding, Lei; Hu, Xia; Wei, Lili; Sun, Mojian; Sun, Guixia; Jiang, Guangfeng; Li, Huanting
Abstract : Objectives: To separately examine and comprehensively compare the risk factors for hospital-acquired (HAPIs) and community-acquired pressure injuries (CAPIs). Design: A mixed case–control study. Setting: Four medical centres in China. Participants: Inclusion criteria included patients who were (1) aged ≥18 years on admission; (2) admitted between January 2014 and December 2018, and (3) diagnosed with HAPIs (cases) or with no HAPIs (controls) during hospitalisation in the HAPIs study, and confirmed with CAPIs (cases) or with no PIs (controls) on admission in the CAPIs study. The exclusion criteria were as follows: (1) admitted for childbirth, psychiatric reasons or rehabilitation; (2) admitted for observation; (3) transferred from another hospital and (4) confirmed to have suffered PIs from previous hospitalisations in the CAPIs study. In total, 320 cases and 1657 controls were included in the HAPIs study, and 1763 cases and 1786 controls were included in the CAPIs study. Primary and secondary outcome measures: The outcome variable was the occurrence of PIs. Results: The existence of PIs or scars from previous PIs on admission, presence of forced posture, use of medical devices and surgery during hospitalisation were found to be independent risk factors for HAPIs, as evidenced by the corresponding OR and 95% CI values of 51.931 (34.241 to 78.763), 2.006 (1.405 to 2.864), 3.226 (1.709 to 6.089) and 2.161 (1.452 to 3.215), respectively. Age, sex, Braden rating and diabetes were found to be independent risk factors for CAPIs, as evidenced by the corresponding OR and 95% CI values of 1.031 (1.026 to 1.036), 0.810 (0.698 to 0.941), 1.235 (1.167 to 1.307) and 2.059 (1.332 to 3.184), respectively. Conclusions: The existence of PIs or scars from previous PIs on admission, presence of forced posture, use of medical devices and surgery during hospitalisation are suggested to be included as independent items for the risk assessment of PIs, together with the Braden scale. The Braden rating plays different roles in the development of CAPIs and HAPIs.